Assessment of Gastric Glandular Atrophy, Intestinal Metaplasia, and Dysplasia Among Patients Underwent Upper GIT endoscopy - Alsafi, Rasha Abdelraouf (Karbala Journal of Medicine, 2021)
Abstract: the current study is reflecting the commonness of gastric precancerous lesions as glandular atrophy, intestinal metaplasia and gastric dysplasia in a set of Iraqi patients underwent upper GIT endoscopy. As Helicobacter pylori infection was regarded as one of the predisposing factor for gastric adenocarcinoma many trials and studies were performed for the diagnosis of H. pylori infection globally. The aim of the study is to assess the prevalence of H. pylori infection, atrophy, intestinal metaplasia, and dysplasia in patients with gastric biopsy and to highlight the correlation of each of the age of the patients and the H. pylori infection with precancerous histopathological parameters. Finally to investigate the association between metaplastic and dysplastic changes in the examined biopsies. Methods: The data was gathered from patients from January to September 2019 in Al Hussein teaching hospital and several private laboratories. It includes (414) patients who were subjected to esophagogastroduodenoscopy (EGD) in this period. From all patients endoscopic mucosal biopsies were obtained. Every biopsy has minimally two mucosal segments that subjected to a standard histological processing and stained with hematoxylin-eosin stain to diagnose the gastric mucosal changes. Giemsa stain was used to detect H. pylori organisms in all biopsies. Results: The mean age of patients was (39.97 +/- 14.5 years SD). All patients have gastritis 414 (100%) and H. Pylori infection was detected in 301 (72.7%) patients. From all patients; 95 (22.9%) were presented with glandular atrophy; thirty six patients (8.7%) had intestinal metaplasia and only 6 (1.4%) patients had dysplastic changes. There was a significant statistical relation between each of gastric glandular atrophy and gastric intestinal metaplasia with age, p value (0.01) for each. there was a significant statistical relation between glandular atrophy and infection with H. Pylori, p value (0.001). A significant negative relation between H. Pylori infection and the presence of intestinal metaplasia, p value (0.0001) was observed meanwhile there was a significant correlation between the intestinal metaplasia and dysplastic changes, P value (0.001). Conclusion: The current study spot a light on the prevalence of H. pylori infection and clarify how common the gastric changes (atrophy, metaplasia and dysplasia) can be detected in a set of patients attending the health institute with chronic gastritis and subjected to esophagogastroduodenoscopies in holy Karbala. There was a significant relation between the age and gastric glandular atrophy and intestinal metaplasia, a negative significant relation between H.Pylori infection and intestinal metaplastic changes. There was a significant relation between intestinal metaplasia and gastric dysplasia.